The Effect Of Capital Structure, Company Growth and Profitability on Company Value with Dividend Policies as Interventing Variables to Manufacturing Companies Registered on The IDX for the 2009-2018 Period: The Effect Of Capital Structure, Company Growth and Profitability on Company Value with Dividend Policies as Interventing Variables to Manufacturing Companies Registered on The IDX for the 2009-2018 Period - Nova Sabrina; Rina Bukit; Candra Situmeang (Institute of Computer Science (IOCS), 2020)
Firm value is investors 'perceptions of the company's success related to debt prices that are relatively used for equity funding. Company value reflects investors' views on a company's success rate which is often associated with stock prices, so that if the stock price is high, the company value can be high. This study aims to analyze the influence of capital structure, company growth and profitability as factors that affect firm value in manufacturing companies that carry out Initial Public Offering (IPO) policies for the 2009-2018 period. This research will also examine the dividend policy variable which is used as a mediating variable in the research model.The population is the companies implementing Initial Public Offering (IPO) policies for the 2009-2018 period. The population of this study was 166, the sample selection method used in this study was purposive sampling method with a total of 38 companies that met the criteria. The types of data used were secondary data and the data were analyzed using cross-sectional data analysis techniques and Interaction Moderating Test with the help of Eviews 9 software.The results of this study indicate that at ? 5%, capital structure, company growth, and profitability have a significant effect on company values. The results of this study also show that dividend policy is able to mediate the capital structure and profitability of firm value, on the other hand, dividend policy is not able to mediate company growth on firm value.